Antibacterial and fluorescent clear aligner attachment resin modified with chlorhexidine loaded mesoporous silica nanoparticles and zinc oxide quantum dots. (May 2023) - Cao, Lingyun; Yan, Jiarong; Luo, Ting; Yan, Huiyi; Hua, Fang; He, Hong
Abstract: Objectives: To develop an antibacterial and fluorescent clear aligner attachment resin via the incorporation of chlorhexidine loaded pore-expanded mesoporous silica nanoparticles (CHX@pMSN) and amino-silane functionalized zinc oxide quantum dots (aZnOQDs ), and to evaluate its antibacterial activity, fluorescence capability, esthetic properties, mechanical performance and biocompatibility. Methods: CHX@pMSN and aZnOQDs were incorporated into the commercial resin composites (Filtek Z350 XT, 3M) at different mass fractions, control group: Filtek; fluorescent attachment resin (FAR): Filtek + 3 wt% aZnOQDs ; antibacterial and fluorescent attachment resin (AFAR)-1: Filtek + 3 wt% aZnOQDs  + 1 wt% CHX@pMSN; AFAR-2: Filtek + 3 wt% aZnOQDs  + 3 wt% CHX@pMSN; AFAR-3: Filtek + 3 wt% aZnOQDs  + 5 wt% CHX@pMSN. CHX release, antibacterial activity, fluorescence capability, color change, stain resistance, degree of conversion, depth of cure, polymerization shrinkage, water sorption and solubility, softening in solvent, flexural strength, flexural modulus, shear bond strength, and cytotoxicity were evaluated comprehensively. Results: CHX could be continuously released from the AFAR groups for up to 30 days. CFU, MTT, lactic acid production, SEM and CLSM evaluation showed AFAR-2 and AFAR-3 could effectively inhibit S. mutans biofilms even after 1-month aging. Only AFAR-3 showed clinically perceptible color change and all the experimental groups were not more susceptible to staining. AFAR-1 and AFAR-2 could suppress polymerization shrinkage and enhance the resistance to degradation without compromising other properties, including degree of conversion, water sorption and solubility, flexural strength, flexural modulus, and shear bond strength. Depth of cure of all the four experimental groups was significantly decreased (p < 0.05) but still within the ISO standard. CCK-8 assay and live/dead cell staining denied the cytotoxicity of experimental resins. Fluorescence intensity tests showed that FAR and AFAR-2 could emit strong yellowish fluorescence under the excitation of ultraviolet for up to six months. Conclusions: AFRA-2 possessed long-term antibiofilm activity, strong fluorescence capability and satisfying biocompatibility without compromising esthetic and mechanical properties. This study proposed a new strategy for reducing bacteria accumulation around the attachment, which is also promising in helping orthodontists to remove the attachment thoroughly and precisely.